2012
DOI: 10.2334/josnusd.54.279
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid profile of saliva from patients with oral squamous cell carcinoma using high performance liquid chromatography

Abstract: Oral cancer is the leading cause of death worldwide and it is the eighth most common cause of cancer death. Cancer cells utilize more glucose and amino acids than their benign counterparts. Diagnosis of disease via the analysis of saliva is potentially valuable, as the collection of fluid is associated with fewer compliance problems than the collection of blood. Hence, the present study was undertaken to evaluate the comprehensive amino acid profiling of saliva by high performance liquid chromatography (HPLC).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…To our knowledge, this is a first study employing saliva for metabolic biomarker discovery in dementia. Reddy et al reported that most amino acids, including arginine and tyrosine, were significantly increased in saliva from oral squamous cell carcinoma patients . However, the biological mechanism involved in the decreased arginine and tyrosine levels in saliva of dementia patients is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, this is a first study employing saliva for metabolic biomarker discovery in dementia. Reddy et al reported that most amino acids, including arginine and tyrosine, were significantly increased in saliva from oral squamous cell carcinoma patients . However, the biological mechanism involved in the decreased arginine and tyrosine levels in saliva of dementia patients is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the amide I band was assigned as a discriminant in 14 out of 18 studies, phenyl vibrations in 10 studies, Amide III, phenylalanine, tyrosine in eight studies, and tryptophan, proline in seven studies. Further, several research works have been reported on the profile of amino acids of human saliva and their use in disease diagnosis [ 61 , 62 ]. The varying levels of these amino acids in saliva, related to the degradation of proteins present in saliva, represent interesting markers for pathology detection [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of amino acid and protein constituents, the oral premalignant and malignant saliva have shown the increased level of histidine at 918 cm −1 , valine at 948 cm −1 , proline at 986 cm −1 , nucleic acid vibration at 1460 and 1485 cm −1 and amide I at 1636 cm −1 than that of normal group. Several research works have been reported on the profile of amino acid of human saliva and their use in disease diagnosis . Sugimoto et al reported on the metabolomics of saliva of oral, breast and pancreatic cancer using capillary electrophoresis mass spectrometry and reported that the concentration of leucine, isoleucine, tryptophan, valine, threonine, histidine, alanine and phenylalanine in patients with OSCC were elevated than in normal subjects.…”
Section: Discussionmentioning
confidence: 99%